Comparison Between Ferguson's Technique and Mitchelle Bank Technique for Inguinal Herniotomy in Children - rehman, shafqat; Ahmed, Iftikhar; Awan, Safdar Hussain; Anwar, Zahid; Saleem, Muddasir; Afzal, Tamoor (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the safety of the Mitchelle bank technique for herniotomy in children by comparing its recurrence rate with conventional Ferguson's technique.Study Design: Quasi-experimental study.Place and Duration of Study: Paediatric Surgery Department, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2018 to Sep 2019.Methodology: Children below the age of 6 years coming to Paediatric Surgery Outpatient Department with inguinal hernia were included in the study. The patients were divided into two groups. Group-I underwent herniotomy by Mitchelle bank technique (MBT-group) while Group-II by Ferguson's technique (FT-group). The demographic characteristics of the studied population, operative time, and intra-operative and post-operative complications were recorded.Results: The mean age of the patients was 25.94 ± 17.06 months in Ferguson's technique-group and 24.76 ± 16.63 months in the Mitchelle bank technique-group. The mean operative time was less in the Mitchelle bank technique-group (13.17 ± 1.47 minutes) as compared to Ferguson's technique-group (16.23 ± 1.51 minutes) (p0.05).Conclusion: Mitchelle bank technique is safe for herniotomy in children with less operative time and no increase in...